Roles, reglas y comunicación en familias de conductores de trasporte público que presentan estrés laboral (2018)
In the present investigation there carried out the study of the such familiar dynamics as the communication, roles and rules presented in five drivers' families of trasporte public of the city of Bogotá that they present job stress, for this there was in use a qualitative methodology that allowed to work with a narrative design that realized of the personal experiences of every participant of a sequential way to recognize the principal characteristics studied in the investigation and the technology used for the compilation of information to be an opened interview.